Beyond the Phase Segregation: Probing the Irreversible Phase Reconstruction of Mixed‐Halide Perovskites. Issue 5 (19th December 2021) - Li, Zhe; Zheng, Xin; Xiao, Xuan; An, Yongkang; Wang, Yanbo; Huang, Qingyi; Li, Xiong; Cheacharoen, Rongrong; An, Qinyou; Rong, Yaoguang; Wang, Ti; Xu, Hongxing
Abstract: Mixed‐halide perovskites can undergo a photoinduced phase segregation. Even though many reports have claimed that such a phase segregation process is reversible, what happens after phase segregation and its impact on the performance of perovskite‐based devices are still open questions. Here, the phase transformation of MAPb(I1− x Br x )3 after phase segregation and probe an irreversible phase reconstruction of MAPbBr3 is investigated. The photoluminescence imaging microscopy technique is introduced to in situ record the whole process. It is proposed that the type‐I band alignment of segregated I‐rich and Br‐rich domains can enhance the emission of the I‐rich domains by suppressing the nonradiative recombination channels. At the same time, the charge injection from Br‐rich to I‐rich domains drives the expulsion of iodide from the lattice, and thus triggers the reconstruction of MAPbBr3 . The work highlights the significance of ion movements in mixed‐halide perovskites and provides new perspectives to understand the property evolution. Abstract : Photoluminescence imaging microscopy is employed to investigate the phase transformation of MAPb(I1− x Br x )3 under continuous irradiation. Due to the charge injection from Br‐rich to I‐rich domains, an irreversible reconstruction of MAPbBr3 is induced. This work reveals the mechanisms of photo‐induced phase reconstruction, and deepens the understanding of the stability of mixed‐halide perovskites.